The Role of Women's Coaches in the Development of Women's Sports - Yaqubov Shavkat Maxmudovich (Central Asian Journal of Theoretical and Applied Science, 2022)
This article provides information about the attention paid to women's sports in our country and their role in society. In addition, methods of involving women in physical education and sports and organizing mass sports events among them are described.